New speakers in the context of the minority languages in Europe and the revitalisation efforts - Šatava, Leoš (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2019)
Until recently (socio)linguistic studies concerned with minority languages and efforts at their revitalization focused chiefly on native speakers. By contrast this paper concentrates on new speakers as a relevant current sociolinguistic phenomenon and on postvernacular languages or xenolects formed on this basis. The text examines definitions of new speakers and connected terminology; moreover, it deals with a typology of postvernacular languages, with questions of legitimacy and authenticity, or a possible integration of both groups of users. Prospects of these topics are outlined. Micro case studies on the current situation of new speakers in three small vernaculars of Central Europe (Sorbian, Wilamowicean and Huncokár German) are used as comparative material.
Keywords: domači govorci; jezikovna asimilacija; jezikovna avtentifikacija; jezikovna legitimacija; jezikovna revitalizacija; manjšinski jeziki; novi govorci; študije primerov Srednje Evrope